1991
DOI: 10.1021/bi00225a012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enolase: the crystal structure of enolase-magnesium-2-phosphoglycerate/phosphoenolpyruvate complex at 2.2-.ANG. resolution

Abstract: Enolase in the presence of Mg2+ catalyzes the elimination of H2O from 2-phosphoglyceric acid (PGA) to form phosphoenolpyruvate (PEP) and the reverse reaction, the hydration of PEP to PGA. The structure of the ternary complex yeast enolase-Mg2(+)-PGA/PEP has been determined by X-ray diffraction and refined by crystallographic restrained least-squares to an R = 16.9% for those data with I/sigma (I) greater than or equal to 2 to 2.2-A resolution with a good geometry of the model. The structure indicates the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 24 publications
3
98
3
Order By: Relevance
“…These results were later proved in Lebioda and Reed laboratories when the crystalline structures of yeast enolase and neuron-specific human enolase were established [2,45,46]. Selective mutagenesis of yeast enolase and its recent crystallographic studies revealed that the basic amino-acids Lys345, Lys396, His159, His373, and Arg374 in the catalytic center are important in the mechanism of the reversible transition of 2-PGA to PEP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results were later proved in Lebioda and Reed laboratories when the crystalline structures of yeast enolase and neuron-specific human enolase were established [2,45,46]. Selective mutagenesis of yeast enolase and its recent crystallographic studies revealed that the basic amino-acids Lys345, Lys396, His159, His373, and Arg374 in the catalytic center are important in the mechanism of the reversible transition of 2-PGA to PEP.…”
Section: Discussionmentioning
confidence: 87%
“…During gluconeogenesis (anabolic pathway) the same enzyme as a phosphopyruvate hydratase catalyses the reverse reaction hydration of PEP to 2-PGA. Magnesium ions are a natural cofactor of enolase, essential in maintaining active conformation of the catalytic domain and important in the enzymatic reaction mechanism [2]. Enolase is one of most abundantly expressed cytosolic proteins in many organisms.…”
Section: Introductionmentioning
confidence: 99%
“…indicate positions of conservative amino acid replacement. Residues that are thought to participate in substrate binding (E'73, H382, R383, and K405) are indicated with a closed circle ( 0 ) (Lebioda and Stec, 1991). Conserved amino acid residues (D25', E302, and D3") that are likely to serve as ligands for conformational Mg2+ binding are indicated with plus signs (+).…”
Section: Le E E S N D G S Q K I S G D Q L K D L Y K S F V S E Y P I Vmentioning
confidence: 99%
“…The crystal structures of enolases from Escherichia coli, Homarus gammarus and Saccharomyces cerevisiae have been determined at high resolution (Stec & Lebioda, 1990;Lebioda & Stec, 1991;Duquerroy et al, 1995;Zhang et al, 1997;Chai et al, 2004). The above authors have reported that eukaryotic enolases are dimeric and some bacterial enolases are octameric; furthermore, these enolases have very similar amino acid sequences and three-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%